ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGRAJIN ROTAN KECAMATAN RUMBAI KOTA PEKANBARU - Fahmi ardian Lumban Tobing; Sri Kartikowati; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Rattan crafts has been started since 1980 in the city of Pekanbaru and experiencing an increasing number of entrepreneurs. However, since 2007 rattan business development experience had stagnation reflected from a fixed amount of effort amounted to 35. In 2015 the number of craftsmen rattan has more decreased the amount of effort into 23 attempts (Department of industry and trade of the city of Pekanbaru, 2015). This research aims to know the dominant factors affecting any income craftsmen and to know the constraints experienced craftsmen rattan Rumbai Subdistrict, pekanbaru. Methods in this study i.e. the census method through descriptive analysis approach. The population of this research effort was central rattan crafts that is along JL. Yos Sudarso in Rumbai, Pekanbaru and the sample in this research is the 23 rattan crafts. Based on the results of research, there are four factors that determine the income of craftsmen, it’s. a factor of capital, raw materials, and marketing the results of production. All four of these factors has a value at a certain point that affect and determine the value of the income of the craftsmen rattan.Key words: rattan crafts, craftsmen rattan